2002
DOI: 10.1002/ffj.1073
|View full text |Cite
|
Sign up to set email alerts
|

Identification of green note compounds in malt whisky using multidimensional gas chromatography

Abstract: We studied green note compounds in malt whisky using multidimensional GC-MS-olfactometry (MDGC-MS-O). Two aldehydes and three alcohols were shown to contribute to the green note: E,Z-2,6-nonenal and E-2-nonenal, and 1-octen-3-ol, 4-hepten-1-ol and nonan-2-ol, respectively. Malt whiskies with high green note scores organoleptically contained more of the aldehydes and nonan-2-ol than those with low scores. This is the first time that E,Z-2,6-nonadienal, 1-octen-3-ol, and 4-hepten-1-ol have been identified in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…The applied technique allowed the detection of two aldehydes (( E )‐2‐nonenal and ( E , Z )‐2,6‐nonadienal) and three alcohols (1‐octen‐3‐ol, 4‐hepten‐1‐ol and nonan‐2‐ol) responsible for the green note aroma. It was demonstrated that green note whisky contains more aldehydes and nonan‐2‐ol compared with other whisky types …”
Section: Analysis Of Whisky Compositionmentioning
confidence: 99%
“…The applied technique allowed the detection of two aldehydes (( E )‐2‐nonenal and ( E , Z )‐2,6‐nonadienal) and three alcohols (1‐octen‐3‐ol, 4‐hepten‐1‐ol and nonan‐2‐ol) responsible for the green note aroma. It was demonstrated that green note whisky contains more aldehydes and nonan‐2‐ol compared with other whisky types …”
Section: Analysis Of Whisky Compositionmentioning
confidence: 99%
“…For identifying green note compounds, specifically for detecting two aldehydes (E,Z-2,6, nonenal and E-2-nonenal) and three compounds belonging to the group of alcohols (1-octen-3-ol, 4-hepten-1-ol, and nonanal-2-ol), multidimensional gas chromatography with mass spectrometer coupled with olfactometry (MDGC-MS-O) was used. This technique enabled the identification of compounds present at low concentration levels (Wanikawa et al, 2002).…”
Section: Downloaded By [Rutgers University] At 12:11 11 April 2015mentioning
confidence: 99%
“…However, in many wine samples, unusual aroma profi les can be explained by relatively few aroma compounds ( Table 5. Extensive research has been dedicated to the strong odour-active components responsible for the typical nuances experienced during classical sensory evaluation (Fan and Qian, 2006a). Wanikawa et al (2002) conducted interesting research on the green note compounds in malt whisky using a multidimensional GC coupled with mass spectrometry and olfactometry (GCxGC-MS-O). Three alcohols and two aldehydes probably related to lipid oxidation and degradation were found to contribute to the green scent, namely 1-octen-3-ol, 4-hepten-1-ol and nonan-2-ol, and E,Z-2,6-nonenal and E-2-nonenal respectively.…”
Section: Identifi Cation Of the Impact Aroma Compounds In Alcoholic Bmentioning
confidence: 99%